Measuring Illicit Cigarette Trade: The Case of the Philippines - Austria, Myrna S. (Animo Repository, 2021)
Illicit cigarette trade, or the manufacture, distribution and sale of cigarettes that evade taxes and violate trademarks, persists in the Philippines. Using the residual methods, this study estimated the size of illicit cigarette trade in the country covering the period 2009-2017 and the corresponding tax revenue lost. The estimates show that illicit trade has flourished after the increase in excise tax; thus, undermining the effectiveness of the series of tax policy reforms meant to lower, if not eliminate, tobacco use in the country. The magnitude ranges from 3.3% to 42.8% of total cigarette consumption, depending on the threshold of under-reporting used. In 2017 alone, tax revenue lost ranges from a low Ph11.96 billion to a high of Ph40.0 billion using the underreporting threshold of 10 percent and 40 percent, respectively. However, illicit cigarette trade due to smuggling has decreased over the years. This implies that the source of illicit trade has shifted to domestic origin, or one that is sourced from within the country. The study recommends that the increase in illicit trade should not be an excuse not to increase the excise tax on cigarettes. Instead, the tax policy reforms should be accompanied by strengthening tax administration and strict enforcement of government measures to combat illicit cigarette trade